NPC1 silent variant induces skipping of exon 11 (p.V562V) and unfolded protein response was found in a specific Niemann‐Pick type C patient - Encarnação, Marisa (2022)
Background: Niemann-Pick type C (NPC, MIM #257220) is a neuro-visceral disease, caused predominantly by pathogenic variants in the NPC1 gene. Here we studied patients with clinical diagnosis of NPC but inconclusive results regarding the molecular analysis. Methods: We used a Next-Generation Sequencing (NGS)-panel followed by cDNA analysis. Latter, we used massively parallel single-cell RNA-seq (MARS-Seq) to address gene profiling changes and finally the effect of different variants on the protein and cellular levels. Results: We identified novel variants and cDNA analysis allowed us to establish the functional effect of a silent variant, previously reported as a polymorphism. We demonstrated that this variant induces the skipping of exon 11 leading to a premature stop codon and identified it in NPC patients from two unrelated families. MARS-Seq analysis showed that a number of upregulated genes were related to the unfolded protein response (UPR) and endoplasmic reticulum (ER) stress in one specific patient. Also, for all analyzed variants, the NPC1 protein was partially retained in the ER. Conclusion: We showed that the NPC1 silent polymorphism (p.V562V) is a disease-causing variant in NPC and that the UPR is upregulated in an NPC patient.